Reconciling research and implementation in micro health insurance experiments in India: study protocol for a randomized controlled trial - Doyle, Conor (BioMed Central, 2011)
BACKGROUND: Microinsurance or Community-Based Health Insurance is a promising healthcare financing mechanism, which is increasingly applied to aid rural poor persons in low-income countries. Robust empirical evidence on the causal relations between Community-Based Health Insurance and healthcare utilisation, financial protection and other areas is scarce and necessary. This paper contains a discussion of the research design of three Cluster Randomised Controlled Trials in India to measure the impact of Community-Based Health Insurance on several outcomes. METHODS/DESIGN: Each trial sets up a Community-Based Health Insurance scheme among a group of micro-finance affiliate families. Villages are grouped into clusters which are congruous with pre-existing social groupings. These clusters are randomly assigned to one of three waves of implementation, ensuring the entire population is offered Community-Based Health Insurance by the end of the experiment. Each wave of treatment is preceded by a round of mixed methods evaluation, with quantitative, qualitative and spatial evidence on impact collected. Improving upon practices in published Cluster Randomised Controlled Trial literature, we detail how research design decisions have ensured that both the households offered insurance and the implementers of the Community-Based Health Insurance scheme operate in an environment replicating a non-experimental implementation. DISCUSSION: When a Cluster Randomised Controlled Trial involves randomizing within a community, generating adequate and valid conclusions requires that the research design must be made congruous with social structures within the target population, to ensure that such trials are conducted in an implementing environment which is a suitable analogue to that of a non-experimental implementing environment.